Lecturer Competence in The Digital Era : Are Lecturers Able to Utilize Artificial Intelligence-Based Learning Media in The Civic Education Learning Process? - Nuryadi, Muhammad Hendri; Widiatmaka, Pipit; Hed, Norhafiza Mohd (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to explore the competence of lecturers to face the challenges of artificial intelligence, the use of artificial intelligence-based learning media in the learning process of civic education, and the constraints of lecturers in utilizing artificial intelligence-based learning media. This research uses a qualitative approach with descriptive methods and data collection techniques using interviews, observation, and documentation. The subjects in this study are lecturers who teach civic education courses. The data analysis used was content analysis, and this research was conducted at Universitas Sebelas Maret, Indonesia. The results showed that in facing the challenges of the era of artificial intelligence, a lecturer, in addition to having pedagogic, professional, social, and personality competencies, must also have learning and innovation skills, digital literacy skills, and career and life skills. The use of artificial intelligence-based learning media at Universitas Sebelas Maret in the learning process is still relatively less than optimal because there are still some lecturers who do not utilize artificial intelligence technology. The obstacle faced by lecturers in utilizing artificial intelligence-based learning media is that there are still lecturers who cannot operate artificial intelligence technology, so the impact on student learning motivation is reduced. This phenomenon will have implications for the weak civic competence in students, especially civic skills so that they will experience obstacles in facing the development of the times.